Immunohistochemical expression of vascular endothelial growth factor in orofacial lesions - A review - Bhavana Gupta; Shaleen Chandra; Vineet Raj; Vivek Gupta (Elsevier, 2016)
Angiogenesis is considered to be an important biological process in disease progression and tumorigenesis. Among the various factors associated with angiogenesis, vascular endothelial growth factor (VEGF) is a leading candidate. VEGF induces the proliferation, differentiation, and migration of vascular endothelial cells, increases capillary permeability, and enhances endothelial cell survival by preventing apoptosis. This article reviews and highlights the role of VEGF in health, and various oral diseases.